AB0401 Combined drug-rehabilitative treatment in rheumatoid arthritis. (23rd January 2014) - Di Gioia, L.; Zincarelli, C.; Iervolino, S.; Vitale, D.F.; Pappone, N.
Abstract : Background: Rheumatoid Arthritis may lead to structural alterations with severely impaired function. Biologic DMARDs reduce signs and symptoms, but fail in reducing the established joint damage and in improving impaired function. Recent reports show the efficacy of rehabilitative programs in RA patients, by affecting pain, stiffness and fatigue Objectives: assess the effectivenessof a combined drug-rehabilitative treatment in ameliorating function and fatigue in RA patients Methods: 40 RA patients treated with biologic DMARDs, with severely impaired function were enrolled. From the enrollment (T0) all subjects underwent to a 3-weeks rehabilitative program. They were followed-up at the end of treatment (T1), 3 (T2), 6 (T3) and at 9 (T4) months, evaluating: TJC, SJC, DAS-28, ERS, HAQ, GH and FACIT. Results: all the outcomes significantly improved from T0 to T4 (Tab. 1). Conclusions: the combined treatment is effective in reducing function impairment. This approach ameriorated joint pain, muscle-tone, and improved the resistance to fatigue, even if unmodifying the biologic DMARDs. These effects were kept over the time. FACIT resulted to be an independent variable from disease activity parameters. In conclusion, the combined treatment results in a durable improved function and resistance to fatigue regardless disease activity. References: Harris ED Jr. Rheumatoid arthritis: pathophysiology and implications for therapy. N Eng J Med 1990; 322: 1277-1289 Disclosure of Interest: None Declared